A low-cost narrow-beamwidth DBF radar concept - Tang, Yue. (2013)
An innovative low-cost and higher than conventional angular resolution digital beamforming (DBF) array radar system is proposed and introduced in this paper. The proposed DBF radar system uses only one set of transceiver plus an additional microwave switch. Compared with conventional configurations with N sets of expensive microwave digital transceivers, the proposed concept can drastically reduce the system cost. Besides, we also propose an innovative DBF scheme that has narrower beamwidth the the conventional one-way or two-way beamforming configurations. The total system cost reduction factor is up to 2 times the number of array elements.